Spatial targeting, synergies and scale: Exploring the criteria of smart practices for siting renewable energy projects. (September 2018) - Frantál, Bohumil; Van der Horst, Dan; Martinát, Stanislav; Schmitz, Serge; Teschner, Na´ama; Silva, Luis; Golobic, Mojca; Roth, Michael
Abstract: Policies and strategies to develop renewable energy and the rates of successful deployment vary from country to country. Academic literature is rife with examples of recurring problems and malpractice in the implementation of renewable energy projects. We could see each national and sectoral effort as an 'experiment' in the early phase of our attempted transition to a low carbon energy system. What lessons can we learn from a comparative analysis of these experiments? This paper seeks to draw generic lessons not from what has gone wrong but from national case studies that stand out in a best way. Through a European academic network, we have selected and analysed 51 'smart practice' case studies of renewable energy development from 20 countries. We present the outcomes of both qualitative and quantitative analysis of these case studies (smart practice criteria) and discuss a set of generic findings concerning specific types of smart practices and problems of potential transferability of projects to other regions. With regards to policy relevance, the findings can be used for evaluating portfolios of renewable energy projects developed to date and for setting guiding principles for project design, spatial planning and consent by means of cross-national learning and fertilization. Highlights: We classify criteria of smart practice in renewable energy implementation. Proper spatial targeting, synergies and scale are key criteria of smart practice. We discuss potential transferability of local smart projects to other regions. Practical relevance for guiding principles for spatial planning & project design.